Clinicopathological Significance of Vimentin and Cytokeratin Protein in the Genesis of Squamous Cell Carcinoma of Cervix - Nazik Elmalaika O. S. Husain; Ali Yousif Babiker; Aqel S. Albutti; Mohammed A. Alsahli; Salah M. Aly; Arshad H. Rahmani (Hindawi Limited, 2016)
Cervical cancer is one of the commonest types of cancers worldwide especially in developing countries. Intermediate filaments protein family has shown a role in the diagnosis of various cancers, but a few studies are available about the vimentin and cytokeratin roles in the cervical cancer. This case control study aimed to interpret the expression of vimentin and cytokeratin proteins in the development and progression of cervical cancer and its correlation with clinicopathological features. The cytoplasmic expression of vimentin was observed in 40% of cases, but not in inflammatory lesions of cervix. It was noticed that vimentin expression was increasing significantly with high grade of the tumour. Cytokeratin expression was observed in 48.33% and it was noticed that the expression was 62.5% in well differentiated (G1), 45% in moderately differentiated (G2), and 41.66% in poorly differentiated carcinoma, yet statistically insignificant. The expression of vimentin and cytokeratin proteins was not significantly associated with age groups. The current findings concluded a possible role of vimentin in the development and progression of cervical cancer and vimentin marker will be useful in the diagnosis and grading of cervical cancer.